The development of food frequency questionnaire and assessment of 15-year-old Malaysian adolescent dietary intake / Khairunnisa Mohamed - Khairunnisa, Mohamed (2018)
At present, there is a worrisome increasing prevalence of obesity and cardiovascular risk among adolescents in Malaysia, which could have a major impact on the health of the later adult population of the country if no proper action is taken. Although there are several methods available for the assessment of the dietary intake of a population, the food frequency questionnaire (FFQ) is one of the dietary tools commonly used to assess the habitual intake of a population. Different versions of the FFQ are needed to assess different populations’ dietary habits and patterns. The aim of this study was to investigate the socio-demographic factors that influence the dietary intake of the Malaysian adolescent population and also to develop a FFQ that suits the multi-ethnic Malaysian adolescent population that can be used in future diet–disease relationship studies. In part one of the study, diet data from the Malaysian Health and Adolescents Longitudinal Research Team Study (MyHeARTs) 2014 database were used to investigate the macroand micronutrient intake of Malaysian adolescents by sex, place of residence, ethnicity, parent’s education, body mass index (BMI) and household income. The nutritional status of the adolescents was also examined. In part two of the study, collective food data from the MyHeARTs 2012 database were used to construct the Malaysian Adolescent FFQ (MyUM Adolescent FFQ). A total of 78 participants aged between 13 and 15 years old in 2014 were selected through convenience sampling for the test-retest study. A total of 156 MyHeART study participants who were 15 years old in 2014 were randomly selected for the comparative validity study. They completed a 7-day diet history (7DDH) and subsequently completed the self-administered MyUM Adolescent FFQ. In part 1 of the study, the mean intake of energy, protein and sodium for both sexes were significantly iv higher than the Malaysian recommended nutrient intake (RNI), while the mean intake of fibre, vitamin D, potassium, calcium, magnesium and phosphorus were significantly lower than Malaysian RNI for both sexes. Although the male adolescent iron intake was adequate, the female iron intake was significantly below the recommended amount. Except for crude dietary fibre, sugar and vitamin D, the boys had significantly higher macro- and micronutrient intake compared to the girls. There were also significant differences in the macro- and micronutrient intakes and in the nutritional status indicators by residency, ethnicity, parent’s education, household income and BMI. In part 2 of the study, the intra-class correlation between the first and second administration of the FFQ was 0.71 to 0.88 for macronutrients and 0.67 to 0.85 for micronutrients. Energy-adjusted correlations for protein, carbohydrate, and fat were 0.54, 0.63 and 0.49, respectively. Cross-classification analyses revealed that more than 70 percent of adolescents were in either the same or adjacent quartile of nutrient intake when the data of the 7DDH and the FFQ were compared. No serious systematic bias was evident in the Bland–Altman plots. In conclusion, a comprehensive national strategy is required to deal with the long-term hazard of chronic diseases in Malaysia. The 200-item MyUM Adolescent FFQ that was developed by this study has moderate to good comparative validity for the assessment of most macro- and micronutrients, and therefore can be used in future studies to assess the diet of multi-ethnic adolescents in Malaysia